Considerations on contemporary poetry criticism - Franchetti, Paulo (2016)
The  aim  of  the  text  is  to  reflect  on  a  common  problem  in  criticism  of contemporary poetry: automatic and uncritical use of some vague terms and concepts, which have no real power of evaluation or even description.